Effect of magnetic and electric fields on electrical and magnetic properties of multiferroic BiMnO 3 films - Alrub, Ahmad Musleh; Lim, Kok Geng; Chew, Khian Hooi (Elsevier, 2018)
The effect of magnetic and electric fields on the electrical and magnetic properties of BiMnO3 films within the framework of Landau-Ginzburg theory had been investigated. We also calculated and discussed the hysteresis loops of polarization and magnetization as a function of electric and magnetic fields. The results reveal that, the possibility of electric-field control of magnetization switching, and vice versa. By decreasing the film thickness of BiMnO3 film, it is shown that the coercive fields and remnant order parameters are suppressed.